2009
DOI: 10.1074/jbc.m109.003459
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Properties, and Engineering of the Major Zinc Binding Site on Human Albumin

Abstract: Most blood plasma zinc is bound to albumin, but the structure of the binding site has not been determined. Zn K-edge extended x-ray absorption fine structure spectroscopy and modeling studies show that the major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 51 publications
4
131
0
Order By: Relevance
“…30 Speciation is important when considering the toxic effects of inorganic ions and serum albumin is mainly responsible for binding physiologically occurring Zn 2+ , with Log K values reported in the range of 6.1-7.5. 31 It has been recently shown that in the Please do not adjust margins…”
Section: Resultsmentioning
confidence: 99%
“…30 Speciation is important when considering the toxic effects of inorganic ions and serum albumin is mainly responsible for binding physiologically occurring Zn 2+ , with Log K values reported in the range of 6.1-7.5. 31 It has been recently shown that in the Please do not adjust margins…”
Section: Resultsmentioning
confidence: 99%
“…A comparison between LFMD, previous QM/MM results 83 and experimental data is given in Table 1. These include three root-mean-square deviations (RMSDs) for, respectively, Pt-L bond lengths, the heavy (nonhydrogen) atoms of Pt(II) and its ligands NH 3 and Gua, and of the entire Pt-DNA system. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The droplet simulation of the 1,2-interstrand cisplatin-DNA adduct started from the X-ray structure (PDB code 1A2E).…”
Section: Complexesmentioning
confidence: 99%
“…[3][4][5] Extensive research has been reported which elucidates cisplatin's mechanism of action. 2,[6][7][8][9][10] Upon administration, the relatively high concentration of chloride ions in blood (~100 mM) maintains cisplatin in a neutral state.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, albumin, although it is not directly involved in iron transport, is quantitatively the most important circulating binding protein, and is itself a negative acute phase protein commonly measured in clinical practice. 12 Therefore the aim of the present study was to quantify the impact of the magnitude of systemic inflammation, as evidenced by CRP and albumin, on commonly measured serum biochemical measures of iron status. Furthermore the study was carried out with the aim of developing local guidelines for the interpretation of serum measurements of iron status.…”
Section: Introductionmentioning
confidence: 99%